Continuing Trauma: The Unmet Needs of Trauma Patients in the Postacute Care Setting. Issue 11 (November 2017) - Fakhry, Samir M.; Ferguson, Pamela L.; Olsen, Jama L.; Haughney, Jennifer J.; Resnick, Heidi S.; Ruggiero, Kenneth J.
Trauma care has traditionally focused on prehospital and hospital settings, yet many injured patients report emotional distress in the postacute care setting, which is known to impair recovery. The objective of this study was to assess postdischarge emotional recovery and communication preferences. An observational cohort of 100 adult patients from our Level 1 Trauma Center was surveyed one to two months postdischarge. Among those employed preinjury, 44 per cent had not returned to work. Nearly half screened positive for emotional issues (posttraumatic stress disorder, depression, and/or psychological distress); of these, only 35 per cent considered getting professional help and only 10 per cent received help. The barrier most cited (58%) was cost; 42 per cent did not know how or where to get help. Most participants responded "no" or "I don't know" when asked if they had received information about coping with negative emotions after injury and how to seek help from a doctor to address these emotions. Two-thirds preferred to receive such information via phone call from a health care provider or by text. Eighty-nine per cent owned a cellphone. Our trauma systems are failing to provide comprehensive care or look at the ultimate outcomes of our patients, yet modern technology could provide needed resources to patients in novel ways.